PENGARUH PEMBERIAN BEBERAPA PESTISIDA NABATI UNTUK MENGENDALIKAN JAMUR TULAR BENIH KACANG TANAH (Arachis hypogeae L.) DAN PENGARUHNYA TERHADAP DAYA KECAMBAH BENIH - Muhammad Ali; Sonia (UIR Press, 2021)
Seedborne diseases on peanut seeds can be controlled by using plant leaf extracts which applied by seed treatment. The plants leaf used, such as: sambiloto leaves extract, bay leaves extract, basil leaves extract and guava leaves extract. The aim of this research is to study the effect of application several plants leaf extract and obtain the best extract to control seedborne fungal pathogens on peanut seeds and its effect to germination of peanut seeds. The research has been conducted at the Laboratory of Plant Disease and Greenhouse Experimental Farm at Faculty of Agriculture, Riau University, Pekanbaru. This research has been conducted experimentally by using a completely randomed design (CRD), consisting of 5 treatments, namely: without application of plants leaf extract (E0), sambiloto leaves extract 30% (E1), bay leaves extract 30% (E2), basil leaves extract 30% (E3) and guava leaves extract 30% (E4). The data obtained were statistically analyzed with analysis of variance and to compare the mean of treatments, and Tukey’s test at level 5% was applied. The result obtained 5 isolate seedborne fungus on peanut seeds. The results showed that application of basil leaves extract was able to inhibit the growth of Rhizoctonia sp. (30.25%), Macrophomina sp. (41,00%), Rhizopus sp. (20,25%) and Aspergillus sp. (15,00%), the extract of bay leaves had a higher inhibition of Aspergillus sp. (31.25%). The application of bay leaves extract resulted in a better germination rate of (93.00%). The application of the four plants leaf extract were not able to affect the total normal germination seeds and seedling height.